THE EFFECT OF WORK PRESSURE AND CONFLICT ON QUALITY OF WORK AT PT. BANK SULUTGO PAAL DUA SUB-BRANCH OFFICE - Kezia Natalie Tesyalonica Wantania (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2022)
The quality of a company is determined by how well its resources can handle pressure and work conflicts. The subjects in this study were employees at PT. Bank SulutGo Paal Dua Sub-Branch Office, a company engaged in financial management or banking administration. This study aims to find out the pressures and conflicts between employees at PT. Bank SulutGo Paal Dua Sub-Branch Office and how to overcome these pressures and conflicts to improve the quality of the company's work. The study was designed as qualitative research and used descriptive data exposure. Work pressure is an unavoidable demand in a temporary work environment. At the same time, conflict is a social process between two or more people in which one party tries to get rid of the other party by destroying him or making him helpless. These two processes that occur will cause other work to be delayed and disrupt employees' focus. So companies should apply the quality of cooperation and behavior to improve the pressures and conflicts they face.